Oral health of low-income pregnant women in a community of a São Paulo municipality: problems perceived and access to treatment - Rosa Áurea Quintella Fernandes; Nadia Zanon Narchi (Online Brazilian Journal of Nursing, 2008)
An exploratory descriptive study whose purpose was to verify oral health problems perceived by low-income pregnant women in a community of a São Paulo municipality, as well as their access to treatment during pregnancy. The sample consisted of 169 women who participated in the pregnant women´s group in the São Lucas Nucleus for Women’s Health Care, from August 2004 to April 2007. Results showed that the pregnant women’s mean age was 23.7 years, with an age variation of 14 to 42 years, 21.8% of which were adolescent. The educational level was low, as only 16% had concluded the eighth grade, 15.3% had finished high school and 49.7% had not completed the basic education program. Only 10.6% were employed and the family income was 1.4 times the minimum wage. Regarding the perception of oral health problems, 44.9% of the sample identified some problems, such as pain (35.5%), dental cavities (27.6%) or gum bleeding (19.7%). Of the pregnant women who reported problems, only 39.4% sought professional help. Among these, 63.3% did not obtain access to treatment because they were unable to get dental appointments (70%) or due to the fact that they were pregnant (13.3%). It was therefore concluded that, at least in this community, full procedures to assist pregnant women are not being adequately provided. Some women and even some health practitioners erroneously believe that pregnancy represents an obstacle to dental treatments. Therefore, it is necessary to provide better attention from professionals in prenatal assistance regarding the importance of oral health care and its effects on both the women’s and the babies’ health.